Accessibility to Protected Areas Increases Primate Hunting Intensity in Bioko Island, Equatorial Guinea - Branch, Douglas; Moka Sharpe, Silvia; Maho, Luís Miguel; Silochi Pons, Miguel Ángel; Mitogo Michá, Francisco; Motove Etingüe, Amancio; Nze Avomo, Juan Cruz Ondo; Owono Nchama, Pablo Owono; Esara Echube, José Manuel; Fero Meñe, Maximiliano; Featherstone, Bryan; Montgomery, David; et al. (Frontiers in Conservation Science, 2022)
Bioko is one of the most important sites for African primate conservation; yet it has seen a severe decline in its primate populations due to illegal hunting to supply a thriving wildmeat trade. The completion in 2015 of a new road bisecting the Gran Caldera Scientific Reserve (GCSR), where rugged terrain and lack of infrastructure once served as a natural barrier, further threatened this last stronghold for Bioko's primates. Here we used passive acoustic monitoring to study factors affecting hunting patterns within GCSR through the automatic detection of shotgun sounds. Ten acoustic sensors were placed in locations that varied in terrain heterogeneity, distance to the new road, human settlements, research camps (i.e., Moraka and Moaba) and elevation. Sensors recorded continuously between January 2018 and January 2020, collecting 2,671 site-days of audio. In total 596 gunshots were detected, including in the most remote areas. There were significant differences in hunting rate between areas (Kruskal-Wallis, χ2 = 102.71, df = 9, p < 0.001). We also found there were significantly fewer gunshots during 2019 than during 2018 (V = 55, p < 0.001). Occupancy modeling showed that hunting increased with decreasing terrain heterogeneity and decreasing distance to roads and villages; and decreased with increasing proximity to Research Camps. These results demonstrated that increasing accessibility increased primate hunting in GCSR, which was exacerbated by the opening of the new road. We also demonstrated that research presence was effective at reducing primate hunting. Unless strict conservation interventions are implemented, including road checkpoints, increasing biomonitoring and hunting patrols, and an island-wide, enforced ban on firearms, GCSR will see a significant decrease in primate density over the next decade, including the potential extinction of Critically Endangered Pennant's red colobus, whose entire population is restricted to GCSR and is a primary target of hunters.